(3eHGOF GdEbJUGO GdLRFjs - (3eMeO GMeO(B, (3GdSQjJjs ((3GdGScfOQjI(B:s (3GdOGQ GdLGeYjI(B,s, 2004)
(3gPG GdcJGH Yde GdGbJUGO , GdeTcdI GdGbJUGOjI , GdfXe GdGbJUGOjI hMd GdeTcdI GdGbJUGOjI , GdWdH hGdYQV hJhGRf GdShb hHYV GdJWHjbGJ Ydi GdJhGRf GdShb , eQhfGJ GdWdH hGdYQV , JaSjQ Sdhc GdeSJgdc HGSJNOGe fXQjI GdefaYI GdMOjI hHGSJNOGe JMdjd efMfjGJ GdShGA , fXQjI GdGfJGL hOhGd GdGfJGL aj GdaJQJjf GdbUjQI hGdWhjdI , JcGdja GdGfJGL aj GdaJQJjf GdbUjQI hGdWhjdI GdGTcGd GdeNJdaI ddGShGb JhGRf GdeTQhY aj Shb GdefGaSI GdcGedI , JhGRf GdeTQhY aj GdShb GdefGaSI ZjQ GdcGedI , GdWdH Ydi NOeGJ YfGUQ GdGfJGL YQV NOeGJ YfGUQ GdGfJGL hJMOjO CSYGQgGs
(3HjHdjhZQGajG (B: (3U(B.419-420s
Keywords: (3GdGbJUGO GdLRFjs; (3GdGfJGLs; (3GdWdHs; (3GdYQVs